2013
DOI: 10.1007/s00392-013-0555-4
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic score assessment improves cardiovascular risk prediction: the clinical value of SYNTAX and Gensini application

Abstract: The SYNTAX and Gensini score in combination with clinical variables could be used to predict the cardiovascular prognosis during a long-term follow-up of up to 8 years in CAD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
113
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(115 citation statements)
references
References 23 publications
1
113
0
1
Order By: Relevance
“…Although SYNTAX score could be used for this purpose, it has been used frequently to risk-stratify patients with complex CAD undergoing percutaneous coronary intervention. Also, it was previously implied that The SYNTAX and Gensini score in combination with clinical variables could be used to predict the CV prognosis during a long-term follow-up of up to eight years in CAD patients and there is a significant positive correlation between them [29]. Moreover, physicians can include all coronary lesions, which amounts to even less than 50% in the Gensini scoring system, although it is an older scoring system than SYNTAX.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Although SYNTAX score could be used for this purpose, it has been used frequently to risk-stratify patients with complex CAD undergoing percutaneous coronary intervention. Also, it was previously implied that The SYNTAX and Gensini score in combination with clinical variables could be used to predict the CV prognosis during a long-term follow-up of up to eight years in CAD patients and there is a significant positive correlation between them [29]. Moreover, physicians can include all coronary lesions, which amounts to even less than 50% in the Gensini scoring system, although it is an older scoring system than SYNTAX.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Stenosis severity was evaluated based on Gensini scores (GS) 29) by two experienced cardiologists blinded to experimental data. Patients were grouped according to GS tertile (low, GS 18; intermediate, high, GS 41) [29][30][31][32][33] . Demographic data, classical cardiovascular risk factors, laboratory assay results, and previous medical treatment records were collected.…”
Section: Introductionmentioning
confidence: 99%
“…6 Sinning C et al also proposed that both Syntax scoring system and Gensini scoring system in combination with clinical variables could be used to predict the cardiovascular prognosis in CAD patients even during long-term follow-up. 7 Gensini coring systems therefore appear to be a valid estimate of CAD plaque burden. 6 Similar to our findings, Sinan DO et al also found association of serum uric acid level with the presence and severity of CAD.…”
Section: Discussionmentioning
confidence: 98%